1984
DOI: 10.3109/10641968409046068
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein-Kinins in the Central Nervous System

Abstract: We studied whether the components of the kallikrein-kinin system are present in the central nervous system. We found that human cerebrospinal fluid (CSF) contains free kinins: 53 +/- 15 pg/ml; kininogen: 10.9 +/- 2.1 ng kinin equivalent/ml, and kininogenase activity: 5.0 +/- 2.1 ng kinins/ml/minute. Kininogenase activity was 2-3 fold augmented by preincubation with trypsin. Soybean trypsin inhibitor completely inhibited untreated CSF and partially inhibited trypsin activated kininogenase. Kininogenase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…The identified components include bradykinin (BK), 1 kallikrein, 2 angiotensin converting enzyme or kininase II, 3 and BK immunoreactive neuronal systems. 4 When injected intracerebroventricularly, BK itself produces a range of effects such as behavioral arousal and sedation accompanied by electroencephalographic alterations, 5 cardiovascular changes, 6 and antidiuretic action.…”
mentioning
confidence: 99%
“…The identified components include bradykinin (BK), 1 kallikrein, 2 angiotensin converting enzyme or kininase II, 3 and BK immunoreactive neuronal systems. 4 When injected intracerebroventricularly, BK itself produces a range of effects such as behavioral arousal and sedation accompanied by electroencephalographic alterations, 5 cardiovascular changes, 6 and antidiuretic action.…”
mentioning
confidence: 99%
“…4 - 25 We found that human CSF contains small amounts of kininogen. 6 Although the data clearly suggest that increases in brain kinins mediate the cardiovascular effects of melittin, we could not obtain evidence that CSF withdrawn from the cisterna magna at the end of the melittin infusion contains large amounts of kinins. These data contrast with those obtained by Thomas et al, 5 who performed ventriculocisternal perfusions in dogs and found that melittin increased kinins several times in the perfusate.…”
Section: Figure 3 Line Graphs Showing Effect Of Intracerebroventricumentioning
confidence: 66%
“…1 -3 A messenger RNA (mRNA) that codes for a kallikrein-like enzyme 4 has been isolated from brain homogenates; kininogen and free kinins are found in the cerebrospinal fluid (CSF) in dogs and humans, 5 - 6 and several enzymes capable of inactivating kinins are found in the central nervous system as well. heart rate 9 -10 as well as the release of antidiuretic hormones.…”
mentioning
confidence: 99%
“…Both these sys tems work by the mechanism of stress response and produce peptides having an immunomodulant effect. In drug-addicted pregnancies psychophysical and pharmacological stress causes an involvement of the neuroendocrinological and immune systems [15][16][17][18][19][20][21]. Moreover, the kinine-kininase system is involved in the microvascular adaptation to stress [22,23].…”
Section: Drug-addicted Pregnant Patientsmentioning
confidence: 99%